ANALISIS AKSESIBILITAS PENDIDIKAN AGAMA ISLAM UNTUK MAHASISWA TUNANETRA DI PUSAT LAYANAN DISABILITAS UNIVERSITAS BRAWIJAYA - Putri Zahirah; Eko Setiawan; Atika Zuhrotus Sufiyana (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Education is a right for everyone, not least for children with special needs (disabilities), one of the most important things when carrying out education is ease of access. Limited access to higher education for people with disabilities, causing less than one percent of people with disabilities have a diploma S1 they are entitled to education in accordance with their talents and potential. In addition, it is equally important to be accompanied by Islamic Religious Education to be balanced, where religion as a foundation that can form taqwa, morals, giving signs in life, and so on. From these problems, the researcher formulated problems related to accessibility during PAI learning, obstacles, and attitudes and understanding of pre, current, and post-learning students. This research was conducted in Brawijaya University with descriptive qualitative data collection method.Accessibility services provided by the Disability Service Center of Brawijaya University for PAI lectures such as the provision of volunteers , screen reader software, NVDA, book digitization services, sticks, guiding blocks, and the Braille Qur'an. The obstacles experienced by blind students were not too significant, but in certain situations such as reading writing with a font less than 14pt, reading writing on the blackboard, reading and writing Arabic letters, and when working on UTS and UAS participants felt a little difficult. For pre, during, and post-learning PAI, students with visual impairments are fairly active, because participants have prepared what is needed for learning.Â